Acesso, acessibilidade e permanência de pessoas com deficiência no ensino superior: uma pesquisa documental na Universidade Federal do Pará - OLIVEIRA, Lídia Alves (2022)
This article aims to investigate the actions of access, accessibility, and permanence of students with disabilities at the Federal University of Pará (UFPA), through the analysis of the annual reports of the Superintendency of Student Assistance (SAEST). It is documentary research, with a qualitative approach. The research started from the following problem: What are the actions of access, accessibility, and permanence of students with disabilities promoted by the Federal University of Pará (UFPA)? The data collection instruments were the institution's annual reports, from 2010 to 2020. As a result, it can be observed that the UFPA promotes accessibility for students with disabilities by guaranteeing the access and permanence of PwD's students enrolled in the undergraduate course. Through the Accessibility Coordination (COACESS) linked to the Superintendence of Student Assistance (SAEST), educational actions, services, programs, projects, and policies take place. Thus, we can understand the importance of the role of the Higher Education Institution for the access and permanence of people with disabilities in graduation, with emphasis on aspects such as infrastructure, student housing, support for transport, library, cafeteria, and support for students with physical disabilities.